2016
DOI: 10.1007/s13311-016-0429-3
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, Sleep Disorders, and Mild Traumatic Brain Injury. What We Know and What We Need to Know: Findings from a National Working Group

Abstract: Disturbed sleep is one of the most common complaints following traumatic brain injury (TBI) and worsens morbidity and long-term sequelae. Further, sleep and TBI share neurophysiologic underpinnings with direct relevance to recovery from TBI. As such, disturbed sleep and clinical sleep disorders represent modifiable treatment targets to improve outcomes in TBI. This paper presents key findings from a national working group on sleep and TBI, with a specific focus on the testing and development of sleep-related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
129
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 133 publications
5
129
0
Order By: Relevance
“…TBI is defined as an injury that includes transient amnesia, alteration or loss of consciousness that results from a force involving the head or body (Wickwire et al 2016;Mathias and Alvaro 2012). TBI can be classified as mild, moderate or severe based on the presence and severity of the above symptoms, as well as neuroimaging characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…TBI is defined as an injury that includes transient amnesia, alteration or loss of consciousness that results from a force involving the head or body (Wickwire et al 2016;Mathias and Alvaro 2012). TBI can be classified as mild, moderate or severe based on the presence and severity of the above symptoms, as well as neuroimaging characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…TBI can be classified as mild, moderate or severe based on the presence and severity of the above symptoms, as well as neuroimaging characteristics. Reportedly, up to 1.7 million Americans suffers TBI yearly, with 70% of those deemed mild (Wickwire et al 2016;Mathias and Alvaro 2012). Of those who sustain TBI, recent estimates suggest that 30-66% of patients experience some type of sleep disturbance (Wickwire et al 2016;Mathias and Alvaro 2012;Nakase-Richardson et al 2013;Chan and Feinstein 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…70,71 However, these observations have not been confirmed in concussions or mild TBI. 72 Despite the lack of clarity, it is likely that there are multiple interrelationships between the proposed mechanisms. Further research is needed to more completely explain not only the individual roles of these factors but their interrelationships as related to sleep and overall outcomes following concussion.…”
mentioning
confidence: 99%
“…3 In traumatic brain injury patients, subjective complaints of daytime sleepiness and poor sleep quality, as well as poorer sleep efficiency and reduced sleep time on polysomnography, are quite common. 4,5 That said, there is evidence that ubiquity of sleep disorders may not be limited to veterans of recent conflicts; in one study, 87% of older veterans, age 55-89, were found to have sleep-disordered breathing. 6 The relationships between sleep and metabolism are plausibly bidirectional and interwoven.…”
mentioning
confidence: 99%